New approach in multipurpose optical diagnostics: fluorescence based assay for simultaneous determination of physicochemical parameters - Moczko, Ewa (Cranfield University, 2009)
The development of sensors assays for comprehensive characterisation of biological samples and effective minimal-invasive diagnostics is highly prioritised. Last decade this research area has been actively developing due to possibility of simultaneous, real- time, in vivo detection and monitoring of diverse physicochemical parameters and analytes. The new approach which has been introduced in this thesis was to develop and examine an optical diagnostic assay consisting of a mixture of environmental-sensitive fluorescent dyes. The operating principle of the system has been inspired by electronic nose and tongue devices which combine nonspecific (or semispecific) sensing elements and chemometric techniques for multivariate data analysis. The performance of the optical assay was based on the analysis of the spectrum of selected dyes with discreet reading of their emission maxima. The variations in peaks intensities caused by environmental changes provided distinctive fluorescence patterns, which could be handled similar to the signals collected from nose/tongue devices. The analytical capability of the assay was engendered by changes in fluorescence signal of the dye mixture in response to changes in pH, temperature, ionic strength and the presence of oxygen. Further findings have also proved the ability of optical assay to estimate development phases and to discriminate between different strains of growing cell cultures as well as identify various gastrointestinal diseases in human. This novel fluorescence-based diagnostic tool offers a promising alternative to electrochemical systems providing high sensitive measurements with broad dynamic range, easy, inexpensive measurements and the possibility of remote sensing and extreme assay miniaturisation. Additionally it does not require reference signal. This new approach can impact on a number of applications such as routine minimal- invasive diagnostics for medical samples, biomedical analysis, pharmaceutical or cosmetic research, quality control and process monitoring of food or environmental samples.